Water Diffusivity and Capillary Conductivity Studies of Some Libyan Soils: Valley Soil in Sidi El-Mesri in the Jaffara Plain - ASSEED, MOHAMED; SOLIMAN, KHALIL (The Libyan Journal of Agriculture, 2023)
For soils in the valley area in Sidi El-Mesri in the Jaffara Plain, moisture characteristic curves were obtained at three depths. Using undisturbed core samples for these three depths water flux versus time curves were matched with the theoretical curves of the solution of the flow equation. From this matching process values of diffusivity and capillary conductivity of soil were calculated. The relation between the capillary conductivity and both tension and moisture content for the soils was obtained. It was found that the soil at the three depths studied releases moisture rapidly with the increasing tension. The surface soil is faster in that respect than the subsoil. If we consider the value of tension = 340 millibar as the value of water at field capacity, the field capacity of surface soil was about 7 % moisture content on volume basis, while for the subsoil the field capacity was about 11.5%, both values are low values for retaining water in soil for growing plants. For this reason irrigation between short intervals is needed to always supply growing plants with ample amount of water. The capillary conductivity versus both tension and moisture content curves for the three depths studied are close to each other. The general conclusion from the capillary conductivity data is that when the soil contains a high amount of water, the capillary conductivity is very high, which indicates that these soils transport water at a high rate when they are close to saturation. When the moisture content decreases in soil a very rapid decline in the value of the capillary conductivity takes place. A 1 /1.000 reduction in the value for hydraulic conductivity was obtained when the moisture content in soil was changed from 20 % on volume basis to 10%. It is concluded that this soil is a very slow medium for transporting water under low water content .This conclusion in part explains why crop plants in such soil show drought symptoms on hot dry days because movement of water in the direction of roots is limited by these low values of capillary conductivity.